The Third Signal Cytokine Interleukin 12 Rather Than Immune Checkpoint Inhibitors Contributes to the Functional Restoration of Hepatitis D Virus–Specific T Cells. (31st October 2016) - Schirdewahn, Thomas; Grabowski, Jan; Owusu Sekyere, Solomon; Bremer, Birgit; Wranke, Anika; Lunemann, Sebastian; Schlaphoff, Verena; Kirschner, Janina; Hardtke, Svenja; Manns, Michael Peter; Cornberg, Markus; Wedemeyer, Heiner; et al.
Abstract : Background.  Hepatitis D virus (HDV) infection affects 15–20 million individuals worldwide and causes severely progressive hepatitis. It is unknown to what extent cellular immune responses contribute to liver disease and control of viral replication in HDV infection. Methods.  Immune cell frequencies and phenotypes were determined in 49 HDV-infected patients, 25 individuals with hepatitis B virus monoinfection and 18 healthy controls. T-cell proliferative and cytokine-producing capacities were analyzed by stimulation with overlapping peptides spanning the large HDV antigen. To restore T-cell responses, blocking antibodies (anti-cytotoxic T-lymphocyte antigen 4, anti-programmed death ligand 1) or proinflammatory cytokines (interleukin [IL] 12) were used. Results.  Immune cell frequencies and phenotypes did not vary between the groups. Exclusively, the senescence marker CD57 was significantly up-regulated in CD8 + T cells from patients with hepatitis delta. HDV-specific T-cell proliferation and cytokine production were weak and could only partly be rescued by blockade of the programmed death 1 pathway. However, a more robust and consistent increase in HDV-specific CD4 + and CD8 + T-cell responses was evident when the third signal cytokine IL-12 was added, which also affected cytomegalovirus- and Epstein-Barr virus–specific T cells. Conclusions.  This investigation of virus-specific T-cell immunity in patients with HDV infection, the largest to date, revealed premature aging of immune cells and impaired T-cell functionality. This could be restored by blocking inhibitory pathways and, in particular, by supplementing with IL-12.